Uwarunkowania działalności gospodarstw wielkoobszarowych po akcesji w opinii kadry kierowniczej - Spiak, Jan (Conditions of Large-Area Farms' Activity after Joining the European Union, in Opinion of Managers, 2005)
The research made is supposed to show differences which occurred on the agricultural market after joining the European Union, and have influence on large-area farms' activity and their estimation by managers. The research of agricultural market in the second half of 2004 showed that an increase of synthetic prosperity index in agriculture and purchase price index in July and August had occurred, however it also showed a decrease of those indexes in comparison to the previous year. In opinions of managers the biggest chance after joining the EU is introducing "equal" direct supplements and access to the EU market, but he biggest danger is a decrease of purchase price index for agricultural materials and an increase of production resources prices.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 285-289